National Mentality: Does It Influence a Language Grammar? - Ilova, Elena; Salkhenova, Alfiya; Galichkina, Elena (Journal of History Culture and Art Research, 2018)
The article shows connection between the national mentality and the formation of grammar on the example of the French, Kazakh, Russian and English languages. It highlights the usage of copular verbs and modality in the first pair of languages, and word order, imperative mood and impersonal sentences in the second. The analysis shows that while teaching grammar of a foreign language, it is essential to combine it with cultural information and to compare two cultures at that point. Such cultural dialogue will ease the conception of the foreign language grammar phenomena and help form grammar competence – one of the means of intercultural communication – assuming the ability of a linguistic persona to elicit, understand and interpret the concepts formed by grammar tools of a foreign language.